Low Parathormone Level After Total Thyroidectomy- Observation of Patient Traits at A Single Institute (Bangladesh Journal of Nuclear Medicine, 2024)
Objective: Surgical debulking of thyroid and neck lymph nodes is the mainstay of differentiated thyroid cancer treatment, during which parathyroid glands are at risk of either removal or vascular insufficiency. The purpose of this study was to evaluate and categorize the total thyroidectomy patients with low parathormone (PTH) levels who were referred for radio-iodine ablation therapy. Patients and Methods: Two hundred seventeen differentiated thyroid cancer (DTC) patients who underwent total thyroidectomy with or without modified neck dissection between February 2020 and December 2022 were evaluated retrospectively. This was a simple observational study. Post-operative levels of serum PTH and calcium were documented, and statistical analysis was performed. Results: Among 217 patients, post-operative low PTH levels were observed in 51.2% and low serum calcium in 27.6% of total patients. Moreover, 50.7% of total thyroidectomy patients and 52.1% of total thyroidectomy patients with modified neck dissection developed low parathyroid hormone levels. The age group most affected by low PTH levels was 25.34 years old. Furthermore, low serum calcium levels were found in 55% of patients who had a low PTH level. Conclusion:  In this study, the 25.34-year-old age group was more likely to develop a post-operatively low PTH level with female sex predilection.Bangladesh J. Nuclear Med. 26(2): 146-150, 2023